AUDIT COMMITTEE DIVERSITY AND EARNING MANAGEMENT AMONG LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of the Management Sciences, 2023)
Recently, numerous financial scandals have shown that many companies produce manipulated financial information. Consequently, regulators have prescribed corporate governance structures to protect investors and to reduce manipulation of earnings by management but there is increase in cases of earning management among listed manufacturing firms in Nigeria. Hence this study tends to specifically ascertain the effect of audit committees’ financial expertise and audit committees’ frequency of meetings on earnings management. This study adopted ex post facto design and generated data from secondary sources. Purposive sampling technique was used to select thirty – one sample size from fifty-eight listed manufacturing firms on the Nigerian Exchange Group as at 31st December, 2022. The study covered the period of 2011 to 2022. The study found that audit committee member financial expertise and audit committee frequency of meetings does not have any significant effect on real earnings management. The study recommends among others that Since numbers of meeting held by audit committee within company accounting year do not leads to minimizing or reducing real earnings manipulation, the committee should be guided by regulatory authorities (Financial reporting council of Nigeria, Nigeria Exchange Group among to others) to be serious minded during their meetings. The audit committee members should not see their position on corporate governance structure as ceremonial position without adhering to law that created the committee.
Keywords: Earnings; audit committee; financial expertise